Commercial bank innovations in small and medium-sized enterprise finance: Global models and implications for Thailand - Tientip Subhanij (Asian Development Bank Institute (ADBI), 2016)
In Thailand, the government has long recognized the importance of small and medium-sized enterprises (SMEs) to the economy and has given a large amount of financial support to this sector. Still, SMEs are not able to catch up with larger enterprises and the constraints to SME financing remain the main topic of policy discussion today. Against this background, the important issue for Thailand may not be about the lack of financial assistance per se but about how to design an appropriate market-friendly business model and supporting scheme to help SMEs gain access to credit on a sustainable basis. Given the success of microfinance around the world, a large number of commercial banks have made a profitable business out of this sector. This paper explores various business models by commercial banks in microfinance and provides policy implications for Thailand. By making use of commercial banks' competitive advantage, Thailand can create a more market-friendly environment for SME financing. This will also ensure that lending to small-business clients is not a burden to the government and is self-sustaining in the long run.
Keywords: G21; E50; 330; SME; Thailand; bank; financing; microfinance; loans; credit; MFI; SFI; financial institution; commercial banking; financial access